Detection of Fetal Stress from Maternal Abdominal Electrocardiogram Signal - Tamilselvi, R; Beham, M. Parisa; Merline, A; Roomi, S.M.M; Saravanan, B; Ruba, T (International Journal of Computer Sciences and Engineering, 2025)
In recent research, recognition of fetal stress is significant in fetal monitoring during pregnancy. In order to evaluate the health of the fetus, a non-invasive fetal monitoring method should be used for measuring the Fetal Heart Rate (FHR).Many methods are available for assessing the FHR. Among these methods, Cardiotocography (CTG) and Fetal Electrocardiogram (FECG) are common methods for monitoring FHR. The most important parameter for determining the fetal health is the FHR. Lot of algorithms are available extracting FECG signals from mothers abdomen. An algorithm is proposed to extract FECG from signals measured from the maternal abdomen. Wavelet transform technique is the most popular and efficient method for determining ECG characteristics. Independent Component Analysis (ICA) and Principle component Analysis (PCA) techniques are used in wavelet transform. This proposed work consists of three algorithms for finding out the fetal heart rate and stress. The proposed algorithm consists of three steps: 1) Abdominal ECG signal (AECG) is acquired from maternal abdomen i.e. Maternal ECG (MECG). 2) FECG signal is extracted by subtracting MECG signal from AECG signal by PCA method. 3) Then fetal R peaks are calculated in extracted FECG signal to detect fetal heart rate. Finally fetal stress is monitored from the measured FHR. The main contribution of our work is the fetal stress analysis from the fetal heart rate